2020
DOI: 10.3390/en13123160
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Effect on Building Performance: A Case Study in New York

Abstract: The evidences of the influence of climate change (CC) in most of the key sectors of human activities are frequently reported by the news and media with increasing concern. The building sector, and particularly energy use in the residential sector, represents a crucial field of investigation as demonstrated by specific scientific literature. The paper reports a study on building energy consumption and the related effect on indoor thermal comfort considering the impacts of the Intergovernmental Panel on Climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Also, the reliance on passive ventilation means, and shading of external windows as a strategy to reduce overheating and discomfort levels in buildings was emphasised by (Dodoo, 2020) for a modern multi-storey building in Sweden and by (Huerto-Cardenas et al, 2021) for an investigation on heritage buildings. Additionally, (Fabbri et al, 2020) suggest that strategies for new designs and renovations and Page| 359 retrofits will be centred on ventilation, thermal insulation and reflectance. The study predicts a considerable risk of multiple grid collapses and blackouts because of a surge in cooling energy demand.…”
Section: Strategies For Reduced Energy Consumption In Buildingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the reliance on passive ventilation means, and shading of external windows as a strategy to reduce overheating and discomfort levels in buildings was emphasised by (Dodoo, 2020) for a modern multi-storey building in Sweden and by (Huerto-Cardenas et al, 2021) for an investigation on heritage buildings. Additionally, (Fabbri et al, 2020) suggest that strategies for new designs and renovations and Page| 359 retrofits will be centred on ventilation, thermal insulation and reflectance. The study predicts a considerable risk of multiple grid collapses and blackouts because of a surge in cooling energy demand.…”
Section: Strategies For Reduced Energy Consumption In Buildingsmentioning
confidence: 99%
“…Most architects and contractors replicate the same designs in different climate zones. In the past decades, the challenge with buildings was to improve indoor thermal comfort through increased fabric insulation; however, in the future, the major challenge will bother on how to reduce overheating risks to ensure acceptable comfort conditions (Fabbri et al, 2020) and reduced GHG emissions. To ensure the existing building stock adapts to changing climate, designers will centre strategies for new designs and renovations on air exchange, fabric insulation and optimisation of reflective surfaces (Fabbri et al, 2020).…”
Section: Performance Of New Building-enhanced Building Envelopementioning
confidence: 99%
See 1 more Smart Citation
“…It can be said that the results are not detailed and comparable with the ones from more sophisticated simulation software. However, as demonstrated in previous studies [47,[73][74][75][76], the development and adoption of a quick, time-saving methodology is not aimed at replacing the use of professional simulation software, but at rapidly exploring alternative design scenarios and solutions during the early stage without investing a huge amount of time and resources to possibly address the design process towards the most promising alternatives, which can be analysed with software simulation at a further stage to obtain more sophisticated, precise and reliable results. This different approach represents a novelty in the current conventional process, considering the gap related to the time invested for simulation purposes which emerged from the literature review.…”
Section: Scope and Objectivesmentioning
confidence: 99%
“…Recent studies have es that the temperature in Harbin and Beijing will increase by 5.5 and 2.7 °C, respecti 2100 [7]. As the climate changes, the performance of buildings will also change found that cooling energy consumption in office buildings does increase with warming [8][9][10][11]. Cooling energy consumption is expected to increase in all five are an increase of 18.5% in Harbin and 20.4% in Beijing [12].…”
mentioning
confidence: 99%